Implementation of a Web-Based Marriage Registration and Referral Information System at the Bandungan Sub-District Religious Affairs Office - Dheavita Reza Artamevia; Aji Priyambodo; Marsiska Ariesta Putri; Andreas Tigor Oktaga (Proceeding of the International Conference on Electrical Engineering and Informatics, 2024)
The purpose of this research is to build a web-based information system for the Bandungan Sub-district Religious Affairs Office (KUA) that covers marriage registration, referral applications and receipt of marriage registration and referral reports. The research method used is the Research and Development (R&D) method. The R&D method is a research method used to produce certain products and test the effectiveness of these methods. In addition, this research uses the proven waterfall theory. The result of this research is to produce a web-based information system that is able to manage integrated marriage and referral registration data using R&D and Waterfall methods. This information system uses the PHP programming language and uses mysql data storage.